Women's views on postpartum testing for type 2 diabetes after gestational diabetes: Six month follow-up to the DIAMIND randomised controlled trial. Issue 2 (April 2016) - Van Ryswyk, E.M.; Middleton, P.F.; Hague, W.M.; Crowther, C.A.
Highlights: Electronic reminders are preferred for type 2 diabetes (T2DM) screening after GDM. Time constraints and inadequate childcare availability are barriers to T2DM testing. A more convenient postpartum T2DM procedure may facilitate greater test completion. Abstract: Background: This study assessed the views of the women who participated in the DIAMIND randomised trial of postpartum SMS reminders to test for type 2 diabetes after gestational diabetes (GDM) on their preferred type of postpartum reminder system and barriers and facilitators to completion of postpartum diabetes testing. Method: A written questionnaire was sent to women with recent GDM who participated in the DIAMIND trial ( n = 276) via post or email at six months after the birth of their baby. Results: 208 women (75%) returned the study questionnaires. Preferred postpartum reminder types were: SMS (67%), email (17%), postal (12%) and voice call (1%). Women who had not yet completed an OGTT indicated that they planned to undertake one in the future (61%). Common barriers to postpartum OGTT completion included: not having enough time (73%), inadequate childcare (30%), and a need to focus on the health of the baby (30%). The most common facilitator was having a shorter test (33%). Conclusions: Improved childcare quality and access as well as more research into a shorter, more convenient test procedure for type 2 diabetes screening are needed. Reminder systems for postpartum diabetes screening should be electronic where possible.